Fabrication of Fe3O4@SiO2 nanocomposites to enhance anticorrosion performance of epoxy coatings†. (5th November 2015) - Zhang, Chunli; He, Yi; Xu, Zhonghao; Shi, Heng; Di, Haihui; Pan, Yang; Xu, Wei
Abstract : SiO2 ‐coated Fe3 O4 (Fe3 O4 @SiO2 ) nanocomposites were prepared by sol–gel method, and the anticorrosion performance of composite coatings was discussed. The structure of the Fe3 O4 @SiO2 nanocomposites was verified through Fourier transform infrared, X‐ray diffraction, and scanning electron microscopy. Composite epoxy coatings with same concentrations of Fe3 O4 and Fe3 O4 @SiO2 were measured by scanning electron microscopy contact angle meter. More importantly, the Fe3 O4 @SiO2 nanocomposites not only obtained a homogeneous dispersion and compatibility in epoxy resin but also exhibited an obvious superiority in enhancing the anticorrosion performance of epoxy coatings. Furthermore, the anticorrosion mechanism of Fe3 O4 @SiO2 /epoxy composite coating was tentatively discussed. Copyright © 2015 John Wiley & Sons, Ltd.